Complications of Percutaneous Biliary Tract Drainage - Sánchez Rodríguez, Rocío Belén; Belso, Dr. Elián (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Background: Percutaneous drainage of the bile ducts is a minimally invasive diagnostic and treatment procedure that is performed, under anesthesia, in patients with diseases that cause obstruction of the bile duct. It is diagnostic because the cause and precise site of the obstruction can be identified, and therapeutic because it can be resolved in the same surgical procedure. Material and methods: An observational, descriptive, cross-sectional and retrospective study will be carried out, through the study of clinical records of the Dr. Carlos Bonorino Udaondo Hospital, in CABA, Argentina. The study period will include records from 2017 to 2022. The study population will consist of patients with digestive pathologies who receive care at the Dr. Carlos Bonorino Udaondo Hospital. Results: 100 cases of patients submitted to percutaneous biliary drainage were identified, of the total number of patients, 52% were male and 48% female, they presented between 55 and 80 years of age. The reason for consultation was 43% cholestasis, 28% cholangitis, 17% pruritus, and 12% abdominal pain. 86.6% of the patients had malignant lesions and 13.4% benign. The dilation success rate was 81%. The complications associated with the procedure were: 8% infections and 7%  bleeding. Conclusion: Percutaneous biliary drainage has a high success rate and is associated with a low frequency of complications